2017
DOI: 10.1038/srep41732
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of core-shell Au/Fe3O4 nanoparticles

Abstract: We present a systematic study of core-shell Au/Fe3O4 nanoparticles produced by thermal decomposition under mild conditions. The morphology and crystal structure of the nanoparticles revealed the presence of Au core of d = (6.9 ± 1.0) nm surrounded by Fe3O4 shell with a thickness of ~3.5 nm, epitaxially grown onto the Au core surface. The Au/Fe3O4 core-shell structure was demonstrated by high angle annular dark field scanning transmission electron microscopy analysis. The magnetite shell grown on top of the Au … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Figure 3b,c shows the Fe2p and the Mn2p spectra, respectively. For Fe, the two main peaks Fe2p 1/2 and Fe2p 3/2 at 724.73 eV and 711.13 eV, respectively, indicate the presence of Fe 3+ cations by comparison with the Fe2p 3/2 peaks of Fe 2 O 3 and Fe metal [30,31,32,33]. Two sharp peaks for the Mn2p 1/2 and Mn2p 3/2 at 653.23 eV and 641.43 eV, respectively, indicate the presence of Mn 2+ cations by comparison with the MnO [34].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3b,c shows the Fe2p and the Mn2p spectra, respectively. For Fe, the two main peaks Fe2p 1/2 and Fe2p 3/2 at 724.73 eV and 711.13 eV, respectively, indicate the presence of Fe 3+ cations by comparison with the Fe2p 3/2 peaks of Fe 2 O 3 and Fe metal [30,31,32,33]. Two sharp peaks for the Mn2p 1/2 and Mn2p 3/2 at 653.23 eV and 641.43 eV, respectively, indicate the presence of Mn 2+ cations by comparison with the MnO [34].…”
Section: Resultsmentioning
confidence: 99%
“…It occurs typically in thin film bilayers, reflected in the unidirectional anisotropy of the AFM layer coupled with interfacial magnetic moments of the FM layer upon cooling to the Néel temperature in an applied magnetic field . Intensive studies of EB effect on core‐shell nanostructures have been conducted to find efficient means for nanoscale miniaturization of magnetic devices . Many efforts have been made to realize the EB effect on bulk ceramic materials by taking advantage of a simple synthesis procedure.…”
mentioning
confidence: 99%
“…Felix et al [ 74 ] reported the preparation of spherical Au-Fe 3 O 4 core-shell NSs using thermal decomposition method. They mixed both ferric acetylacetonate and auric acetate salts in 1-octadecene and 1,2-hexadecanediol in presence of oleylamine and oleic acid surfactants.…”
Section: Structure and Synthesis Of Magneto-plasmonic Nanostructurmentioning
confidence: 99%
“…Indeed, the interface region between the iron oxide and gold includes broken bonds, which may generate randomness and/or frustration in the exchange interaction between the outer magnetic cations and the inner ones [ 90 ]. In some cases, an exchange bias feature can be observed as illustrated in Figure 20 , with the appearance of a small shift, along the field axis, of the hysteresis loop recorded in FC conditions by comparison to that recorded in ZFC ones [ 74 ]. The iron oxide crystal size reduction leads also to surface iron cation spin disorder, which affects the total magnetic behaviour of the Fe 3− x O 4 matter, decreasing the whole magnetization and increasing the total anisotropy.…”
Section: Magneto-plasmonic Properties Of Fanss and Afnssmentioning
confidence: 99%
See 1 more Smart Citation